On the Absolute and Relative Pessimistic Inductions: A Reply to S. Park. - Hess, Elijah (Problems / Problemos, 2024)
This article explores the pessimistic induction argument against scientific realism, which suggests that because past scientific theories have been proven wrong, we should be skeptical of our current theories. The author examines two versions of this argument, the Absolute Pessimistic Induction (API) and the Relative Pessimistic Induction (RPI), and argues that both are flawed due to the ambiguity of the phrase "earlier theories" in the premises. The text also discusses the arguments of pessimists who aim to disconnect the success of a scientific theory from its truth, known as the Absolute Pessimistic Deduction (APD) and the Relative Pessimistic Deduction (RPD). The author suggests that recent examples of successful theories being false challenge the idea that only realism can explain scientific success.